2023
DOI: 10.3390/su15086976
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Energy Communities’ Awareness on Social Media with a Content and Sentiment Analysis

Abstract: The development of energy communities has the potential to support the energy transition owing to the direct engagement of people who have the chance to become “prosumers” of energy. In properly explaining the benefits that this phenomenon can give to the population, a key set of channels is represented by social media, which can hit the target of citizens who have the budget to join the energy communities and can also “nurture” younger generations. In this view, the present work analyzes the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…The tool can capture and summarise expressed preferences, analyse time series, optimise resources, design plans, predict trends, prepare reports, decrease reputational risks, analyse stakeholder attitudes, and solve problems using big data (Lytras et al, 2017;Troisi et al, 2018). Information was collected from various online sites, including Twitter, Instagram, blogs, forums, Googleþ, online newspapers, Pinterest, YouTube, and others, over 12 months basing on Artificial Intelligence approach (Carat u et al, 2023). The tool fits the research questions as it enables the bottom-up approach, a crucial element in conducting dialogic accounting (Brown and Dillard, 2015).…”
Section: Research Data and Designmentioning
confidence: 99%
“…The tool can capture and summarise expressed preferences, analyse time series, optimise resources, design plans, predict trends, prepare reports, decrease reputational risks, analyse stakeholder attitudes, and solve problems using big data (Lytras et al, 2017;Troisi et al, 2018). Information was collected from various online sites, including Twitter, Instagram, blogs, forums, Googleþ, online newspapers, Pinterest, YouTube, and others, over 12 months basing on Artificial Intelligence approach (Carat u et al, 2023). The tool fits the research questions as it enables the bottom-up approach, a crucial element in conducting dialogic accounting (Brown and Dillard, 2015).…”
Section: Research Data and Designmentioning
confidence: 99%
“…To bridge these gaps, future research could address the limitations by conducting large-scale studies across diverse populations, examining long-term effects, employing experimental designs, incorporating qualitative methodologies or content and sentiment analysis on sustainable issues [53], as well as other methodologies exploring industryspecific dynamics [54], and considering the evolving context. By addressing these limitations, researchers can contribute to a more robust understanding of the impact of COVID-19 on sustainability behavior and inform businesses and policymakers accordingly.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…These communities can aid the rate of development of the green transition by decreasing the cost, but the handling of RECs could be different if European objectives are prioritized contrary to self-consumption. However, the outcome of a social media study conducted by Caratù et al [24] demonstrated that there is a distinct dearth of interest and awareness among practitioners regarding fundamental components of the energy system or DSM actions. Furthermore, the engagement by ordinary citizens on the subject remains largely unaddressed.…”
Section: Introductionmentioning
confidence: 99%